Effect of Demography Factor and Employee Engagement to Organizational Commitment - Hasanati, Nida (Universitas Medan Area, 2018)
Organizational Commitment is important topic of organizational behavior, as it can affect job satisfaction, organizational citizenship, turn over, and job performance . The purpose of this study is to examine the effect of demographic factors (gender,years of experience ) and employee engagement to organizational commitment . This study used bank employees as many as 200 people, research instrumentuse Organizational Commitment Questionnaire (OCQ) and Utrecht Work Engagement Scale (UWES-17). Analytical technique is use multiple regression and T- test. The result of analysis shows that demography factor and employee engagement simultaneously effect organizational commitment, besides it found that between male and female organizational commitment employees is not different.